The Intersection of COVID-19 and Mental Health: What's the Matter with Ethics? - Siti Hafsyah Idris; Nor Jannah Nasution Raduan; Nurul Azreen Hashim; Nadiah Thanthawi Jauhari; Roslinda Mohd Subbian (Yuridika, 2021)
As the coronavirus (COVID-19) pandemic rapidly sweeps the world, it induces a considerable degree of fear, worry and concern in the population at large, despite the measures taken to contain the spread of the disease through quarantine. Health care providers, the elderly and individuals with underlying health conditions are the most vulnerable to the disease. Nations, even those with advanced resources of medical science, have underestimated the perils of the pandemic. Efforts are focused on understanding the epidemiology, clinical features, transmission patterns and management of the coronavirus disease. One aspect often overlooked, however, is the mental health crisis underpinning the effects of self-isolation/quarantine and the deaths of loved ones, a crisis which becomes increasingly urgent as the number of positive cases in Malaysia grows exponentially each day. With strict preventive measures and restrictions enacted by the Malaysian Government in the form of the nationwide Movement Control Order, the citizens are experiencing a range of psychological and emotional reactions, including the fear and uncertainty of being one of the infected. Many studies have been conducted to identify the state of mental health of vulnerable individuals during this calamity. This raises both ethical concerns and legal issues with regard to the rights of individuals enduring mental illness. This paper explores the ethical issues involved in the research on mental health during the COVID-19 pandemic and the regulatory mechanisms which protect the rights of the persons who have symptoms of mental illness.